Genetic and physiological studies of abortive infections of hydroxymethyluracil-containing bacteriophages in lysogens of temperate Bacillus subtilis bacteriophage SPO2. - Friedman, S O (1976)
Wild-type bacteriophage phie and IS (interference-sensitive) mutants of the related phage SP82G did not productively infect strains of Bacillus subtilis that were lysogenic for temperate phage SPO2. In these abortive infections, the sensitive phages adsorbed to and penetrated the nonpermissive host, phage-directed macromolecular syntheses were initiated, but both viral and bacterial nucleic acid production abruptly stopped about 15 min after addition of the phages. The cessation of RNA and DNA synthesis was preceded or coincident with a reduction in oxygen utilization by the infected cultures. Genetic studies of both phie and SP82G suggest sensitivity to SPO2-mediated abortive infection was controlled by a single gene. A mutant of SPO2, SPO2ehp4-, lysogens of which no longer interfere with the development of SP82GIs, was also isolated. The discovery of this ehp- variant suggests the normal SPO2 prophage synthesized a substance that alters cell physiology in some manner detrimental to SP82GIs development. Since SPO2ehp4- grew on and lysogenized bacteria sensitive to wild-type SPO2, the product of the eph gene was apparently not an essential function of this temperate phage.Overall, these observations exhibit remarkable similarities to the inhibition of T4rII mutants by the product of the rex gene of phage lambda.